The Silver Thread - Duey, Kathleen (New York Aladdin Paperbacks, 2001)
After the unicorn Moonsilver is injured by a hunter's arrow, Heart returns to her village to seek the aid of the healer, Ruth Oakes, but unbeknownst to her, the villainous Lord Dunraven has learned of Moonsilver's existence.
Include Illustrations